OPTIMAL CONTROL OF INVESTMENTS AROUND COURNOT POINT - Y. Aganin (Publishing House of the State University of Management, 2018)
Hree variants of the dynamic model of a duopoly are considered. Here’s one of the stationary points is the Cournot point. We study the movement around these points and the optimal investment control in a linear approximation. The equations of dynamics of variables for equilibrium, developing and crisis markets in a linear approximation are obtained. A quasi-optimal Pareto maximization strategy for the vector prot criterion, using a linear convolution of the criteria along with the linearization of the dierential dynamics equations in the vicinity of the stationary points, is proposed.